Impact of sex on outcomes after cardiac surgery: A systematic review and meta-analysis. (15th November 2021) - Dixon, Lauren Kari; Di Tommaso, Ettorino; Dimagli, Arnaldo; Sinha, Shubhra; Sandhu, Manraj; Benedetto, Umberto; Angelini, Gianni D.
Abstract: Background: Despite advances in cardiac surgery, observational studies suggest that females have poorer post-operative outcomes than males. This study is the first to review sex related outcomes following both coronary artery bypass graft (CABG) and valve surgery with or without combined CABG. Methods: We identified 30 primary research articles reporting either short-term mortality (in-hospital/30 day), long-term mortality, and post-operative stroke, sternal wound infection and myocardial infarction (MI) in both sexes following CABG and valve surgery with or without combined CABG. Reported adjusted odds/hazard ratio were pooled using an inverse variance model. Results: Females undergoing CABG and combined valve and CABG surgery were at higher risk of short-term mortality (odds ratio (OR) 1.40; 95% confidence interval (CI) 1.32–1.49; I 2  = 79%) and post-operative stroke (OR 1.2; CI 1.07–1.34; I 2  = 90%) when compared to males. However, for isolated AVR, there was no difference found (OR 1.19; 95% CI 0.74–1.89). There was no increased risk in long-term mortality (OR 1.04; 95% CI: 0.93–1.16; I 2  = 82%), post-operative MI (OR 1.22; 95%CI: 0.89–1.67; I 2  = 60%) or deep sternal wound infection (OR 0.92; 95%CI: 0.65–1.03, I 2  = 87%). No evidence of publication bias or small study effect was found. Conclusion: Females are at a greater risk of short-term mortality and post-operative stroke than males following CABG and valve surgery combined with CABG. However, there is no difference for Isolated AVR. Long-term mortality is equivalent in both sexes. PROSPERO Registration: CRD42021244603. Highlights: Female sex is thought to be a risk factor for mortality and morbidity after cardiac surgery This study is the first to review sex related outcomes following both coronary artery bypass graft (CABG) and valve surgery with or without combined CABG Females are at a greater risk of short-term mortality and post-operative stroke than males following CABG and valve surgery combined with CABG Following isolated aortic valve replacement, there is no difference in outcomes Long-term mortality is equivalent in both sexes